ANALISIS HASIL PERTANIAN (PADI DAN JAGUNG) MENGGUNAKAN REGRESI LINEAR - Inka Dwi Jayanti (Komunitas Menulis dan Meneliti (Kolibi), 2023)
Agriculture is a tool that assists in increasing domestic agricultural production and increasing domestic food security. Rice and corn are two staple foods that have very important roles for the people of Indonesia. More than 95% of the people consume rice, not only rice but corn is also one of the superior agricultural commodities in Indonesia. Production of corn during the period 1980-2019 was the highest in 2019 amounting to 22.59 million tonnes. Of course, with these figures really shows that rice production in Indonesia is very large and extensive. This is also offset by the availability of land as a support. The analysis uses the linear regression method in order to determine the relationship between land area in influencing the results of agriculture, especially in rice and corn plants. This has the goal of being able to find out how much the production of agricultural products is so that the demand for rice and corn in Indonesia can be fulfilled.